Rituximab plus hyper‐CVAD alternating with MTX/Ara‐C in patients with newly diagnosed mantle cell lymphoma: 15‐year follow‐up of a phase II study from the MD Anderson Cancer Center. (9th December 2015) - Chihara, Dai; Cheah, Chan Y.; Westin, Jason R.; Fayad, Luis E.; Rodriguez, Maria A.; Hagemeister, Fredrick B.; Pro, Barbara; McLaughlin, Peter; Younes, Anas; Samaniego, Felipe; Goy, Andre; Cabanillas, Fernando; et al.
Summary: Intensive chemotherapy regimens containing cytarabine have substantially improved remission durability and overall survival in younger adults with mantle cell lymphoma (MCL). However, there have been no long‐term follow‐up results for patients treated with these regimens. We present long‐term survival outcomes from a pivotal phase II trial of rituximab, hyper‐fractionated cyclophosphamide, vincristine, doxorubicin and dexamethasone alternating with methotrexate and cytarabine (R‐HCVAD/MA). At 15 years of follow‐up (median: 13·4 years), the median failure‐free survival (FFS) and overall survival (OS) for all patients was 4·8 years and 10·7 years, respectively. The FFS seems to have plateaued after 10 years, with an estimated 15‐year FFS of 30% in younger patients (≤65 years). Patients who achieved complete response (CR) after 2 cycles had a favourable median FFS of 8·8 years. Six patients developed myelodysplastic syndrome/acute myeloid leukaemia (MDS/AML) whilst in first CR. The 10‐year cumulative incidence of MDS/AML of patients in first remission was 6·2% (95% confidence interval: 2·5–12·2%). In patients with newly diagnosed MCL, R‐HCVAD/MA showed sustained efficacy, with a median OS exceeding 10 years in all patients and freedom from disease recurrence of nearly 15 years in almost one‐third of the younger patients (≤65 years).